Adverse event profile of lomustine and temozolomide: a descriptive analysis from WHO-VigiAccess - Luo, Hua; Fan, Shaohua; Liang, Lu; He, Youfu; Chen, Jiangjie; Xu, Chenghao; Zhu, Jing; Zhang, Liwei (Frontiers in Pharmacology, 2025)
IntroductionIn gliomas, various oncogenic factors can lead to an imbalance between cell proliferation and apoptosis. Lomustine inhibits tumor cell growth by disrupting DNA replication and repair mechanisms. In contrast, temozolomide, an imidazole tetrazine compound, promotes cell apoptosis through DNA alkylation. The present study aimed to systematically analyze and compare the adverse drug reactions (ADRs) associated with lomustine and temozolomide, as reported in the World Health Organization (WHO) VigiAcess database.MethodsUtilizing a retrospective descriptive analysis design, this study focused on two commercially available anti-glioma drugs. ADR reports pertaining to these medications were collected from the WHO-VigiAccess database. The data collection process involved gathering detailed information on various parameters, including age groups, gender, and geographical distribution of patients involved in the ADR reports. Additionally, the study examined the disease systems and symptoms reported alongside the adverse reactions, as recorded in the annual ADR summaries generated by the WHO. By calculating the proportion of adverse events reported for each drug, this investigation provided a comparative analysis of both the similarities and differences in the adverse reactions observed across the two anti-glioma drugs.ResultsAt the time of the search, a total of 22,854 adverse events (AEs) associated with the two anti-glioma drugs were documented in the VigiAccess database. Lomustine exhibits a higher reporting rate concerning blood and lymphatic system disorders, gastrointestinal disorders, and hepatobiliary disorders. In contrast, Temozolomide has a higher reporting rate for general disorders and administration site conditions, nervous system disorders, and skin and subcutaneous tissue disorders. The top five types of AEs for anti-glioma drugs are as follows: general disorders and administration site conditions (8,825 cases, 38.61%), blood and lymphatic system disorders (7,369 cases, 32.24%), gastrointestinal disorders (5,614 cases, 24.56%), nervous system disorders (5,047 cases, 22.08%), and investigations (4,855 cases, 21.24%).ConclusionThe present comparative observational study indicates that these inhibitors are associated with both common and specific adverse reactions, as documented in ADR reports. Clinicians should formulate individualized treatment plans that consider the adverse reactions linked to various drugs and the specific conditions of each patient, thereby promoting the rational use of these costly medications.